Implementation of Augmented Reality (AR) as a Learning Medium for Introducing Hijaiyah Letters (A Case Study at UMP Kindergarten) - Adrian, Dimas; Ridho Muktiadi; Sigit Sugiyanto; Ermadi Satriya Wijaya (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
In today's digital era, Augmented Reality (AR) technology is increasingly being utilized as a learning medium to increase children's interest in learning, including in introducing hijaiyah letters to kindergarten children. The problem that is often faced is the lack of interactive educational applications that are suitable for this age. This research aims to develop AR based educational applications using the Multimedia Development Life Cycle (MDLC) method, which includes six stages, namely concept, design, material collection, manufacture, testing, and distribution. The application was tested using the black box testing method on various Android devices. The test results show that all features such as camera access, marker scanning, 3D appearance of hijaiyah letters, interactive quizzes, instructions for use, and author information function properly. This application supports learning media that is interactive, fun, and helps children recognize hijaiyah letters better.